2012
DOI: 10.1007/s10725-012-9658-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silicon on growth processes and adaptive potential of barley plants under optimal soil watering and flooding

Abstract: Barley (Hordeum vulgare L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 45 publications
1
23
0
3
Order By: Relevance
“…GPX activity (Fig. 3) that typically shows the highest value among various antioxidative enzymes, fits well with shoot and root values reported in Si-treated barley (Balakhnina et al, 2012). Fluorescence microscopy is a modern and effective tool allowing to see changes of target molecules within tissue that are unable to be obtained by quantitative methods such as spectrophotometry.…”
Section: Discussionsupporting
confidence: 83%
“…GPX activity (Fig. 3) that typically shows the highest value among various antioxidative enzymes, fits well with shoot and root values reported in Si-treated barley (Balakhnina et al, 2012). Fluorescence microscopy is a modern and effective tool allowing to see changes of target molecules within tissue that are unable to be obtained by quantitative methods such as spectrophotometry.…”
Section: Discussionsupporting
confidence: 83%
“…by 4.8 %, citrus species by 12.3 %, longan ( Dimocarpus longan Lour) by 10.7 %, tea ( Camelia sinensis ) by 11.0 %, ginseng ( Panax ginseng ) by 3.2 % and papaya ( Carica papaya ) by 9.7 % . Balakhnina et al ( 2012 ) observed that the application of Si stimulated the growth and biomass production of both shoot and roots in barley. In citrus, the application of Si fertilizers enhanced the growth by 30-80 %, promoted fruit maturation by 2-4 weeks and improved fruit quantity (Meena et al 2014 , and reference therein).…”
Section: Othersmentioning
confidence: 99%
“…Ascorbate peroxidise (AsP) and glutathione reductase (GR) activities and thiobarbituric acid reactive substances (TBARS) content were determined as described earlier (Balakhnina et al, 2009(Balakhnina et al, , 2012a(Balakhnina et al, , 2012b in enzymatic extracts and in crude homogenates of the top leaves. Middle fragments (0.5 g) of the fully developed leaves without the midrib were homogenized manually in a mortar with 4.5 ml of cooled 30 mM K/Na phosphate buffer, pH 7.4, containing 0.1 mM EDTA and 2% PVP (M.м.…”
Section: Methodsmentioning
confidence: 99%